Midiatização da resenha cinematográfica no site Omelete: hipermídia e participação do público - Firmino Júnior, João Batista (2013)
Mediatization arises as an unfinished phenomenon, but with the analysis of some film reviews on audiovisual and textual aspects, and also, viewers comments, we want to understand how the latter, in a given site, has been part of a mediatization process, revealing the overflow of social relations to a means that is increasingly becoming a space, and thus generating the concept of "web-review." Our goal is to discover how this relationship between naturally complex and impure review and Web is generating new media practice, how this influences new production of the message, but also experiences with reviews. As for our method, we have the content analysis, the means and the message, but used in a somewhat formalistic way, allowing a type of analysis that took place according to what our objective is, bringing their problems without an excessively rigid structure. The fact is that we find that this new form of review is not limited to "online textual review" or " online audiovisual review ", but it includes all the Web inset and all the resulting human experiences - this contact with hypermedia and interactive possibilities. Finally, we explain that we analyzed two aspects, and the main message and the return messages from the interacting public, facing a process the process of mediatization of underway reviews, and we have shown that the dimension of "web-review" is not a process that comes after the "online reviews", but that both characterizations coexist, as different dimensions of the same phenomenon.